The Effect of Employee Competency, Hospital Management Information System, and Internal Supervision on Administrative Performance through Work Discipline - Tania Evita Salsabila; Dewi Sri Surya Wuisan (Indonesian Journal of Global Health Research, 2026)
This study aims to examine the influence of employee competence, the hospital management information system (HMIS), and internal control on administrative performance through work discipline at Muhammadiyah Hospital Palembang. This research is essential because administrative performance plays a crucial role in determining service quality, operational efficiency, and hospital governance, especially as hospitals increasingly rely on digital systems and require competent human resources to ensure accurate and efficient administrative processes. A quantitative survey approach was employed, using proportional stratified random sampling to select 200 administrative employees as respondents. The data were analyzed using Structural Equation Modeling (SEM-PLS), and the findings show that employee competence, HMIS, and internal control positively and significantly affect both work discipline and administrative performance, with work discipline serving as a partial mediator. These results emphasize that improving administrative performance requires not only adequate employee capabilities and system support but also strong work discipline in implementing administrative procedures, providing important insights for hospital management in strengthening human resource development and optimizing HMIS utilization.